2020
DOI: 10.1155/2020/3824538
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Characteristics and Failure Mechanism of Siltstone with Different Joint Thickness

Abstract: The mechanics of rock mass is significantly affected by joints, but many existing studies of jointed rocks make simplifications that do not consider the joint thickness. To further study the influence of joint thickness on rock mechanics (mechanical properties, failure mechanism, damage model, etc.), we fabricated jointed siltstone specimens with different joint thickness (5, 10, 15, and 20 mm) and the specimens were subjected to uniaxial compression tests. The effects of joint thickness on the uniaxial compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Broken rock cracks vary from subtle cracks to wide cracks, and these repaired cracks of various widths may have diverse infuences on the mechanical properties of a rock mass [46]. Terefore, investigating the efect on the strength recovery of a ruptured rock mass with diverse crack widths flled with repair grout is signifcant.…”
Section: Introductionmentioning
confidence: 99%
“…Broken rock cracks vary from subtle cracks to wide cracks, and these repaired cracks of various widths may have diverse infuences on the mechanical properties of a rock mass [46]. Terefore, investigating the efect on the strength recovery of a ruptured rock mass with diverse crack widths flled with repair grout is signifcant.…”
Section: Introductionmentioning
confidence: 99%
“…As early as 1967, Wager [2] put forward the concept of layered rock mass in the study of igneous rock, which had an important influence on geological research. Subsequently, many scholars [3][4][5][6][7][8] have conducted a lot of studies on the properties of single-layered rock mass such as shale and sandstone. However, in deep engineering, more and more problems of layered rock masses, which are different from general rock mechanics, have been found.…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al (2016) studied non-penetrating jointed rock mass and developed a dynamic damage constitutive model under uniaxial compression. Li H. G. et al, (2020), Li et al (2021), Li et al (2020b) use siltstone, medium grained sandstone, coarse-grained sandstone and coal in the strata of Bulianta coal mine and Buertai coal mine in Shendong mining area as the research object, and analyzed the influence of interlayer thickness on the mechanical properties of jointed rock. They found that the thickness of the interlayer has a significant effect on the mechanical properties of the jointed coal rock and the interlayer thickness has a significant influence on the mechanical properties of the jointed coal rock.…”
Section: Introductionmentioning
confidence: 99%